A prospective real-world analysis of erenumab in refractory chronic migraine - Lambru, Giorgio; Hill, Bethany; Murphy, Madeleine; Tylova, Ivona; Andreou, Anna P. (Journal of headache and pain, 2020)
Background Clinical trials have shown the safety and clinical superiority of erenumab compared to placebo in chronic migraine (CM). The aim of this analysis is to evaluate the effectiveness and tolerability of erenumab in a real-world setting in patients with refractory CM. Methods This is a prospective single centre real-world audit conducted in patients with CM with and without medication overuse, refractory to established preventive medications, who received monthly erenumab for 6 months. Results Of 164 patients treated, 162 patients (female = 135, mean age 46 ± 14.3 years old) were included in the audit. Patients had failed a mean of 8.4 preventive treatments at baseline and 91% of patients failed Botulinum toxin type A at baseline. The mean reduction in monthly migraine days was 6.0 days at month 3 ( P = 0.002) and 7.5 days at month 6 ( P < 0.001) compared to baseline. The mean reduction in monthly headache days was 6.3 days ( P < 0.001) at month 3 and 6.8 days ( P < 0.001) at month 6. At month 3, 49%, 35% and 13% and at month 6, 60%, 38% and 22% of patients obtained at least a 30%, 50% and 75% reduction in migraine days, respectively. The percentage of patients with medication overuse was reduced from 54% at baseline to 20% at month 3 and to 25% at month 6. Compared to baseline, the mean reduction of Headache Impact Test-6 score was 7.7 points at month 3 (from 67.6 ± 0.4 to 59.9 ± 0.9) ( P < 0.001) and of 7.5 points at month 6 (60.1 ± 1.3) ( P = 0.01). The percentage of patients with severe headache-related disability (HIT-6: 60–78) was reduced from 96% at baseline to 68% after three monthly treatments and to 59% after six treatments. At least one side effect was reported by 48% of patients at month 1, 22% at month 3 and 15% at month 6. Constipation (20%) and cold/flu-like symptoms (15%) were the most frequent adverse events reported. Conclusion Erenumab may be an effective and well tolerated therapy for medically refractory CM patients with and without medication overuse.